2013
DOI: 10.5137/1019-5149.jtn.8517-13.0
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of royal jelly for preservation of implant-releated spinal infection in rat

Abstract: AIm: Implant-related infections are still a significant problem in spinal surgical procedures. Many drugs and methods have been tried to prevent implant-related infections. Our objective in this study was to evaluate whether royal jelly, which was found to hinder the growth of MRSA, has any preventive role in the prognosis of an infection in rats in an implant-related infection model. mATeRIAL and meTHods: Rats were divided into 3 groups of eight rats. Group-1 consisted of rats that underwent only a spinal imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In an in vivo experiment on a mouse model, they showed that jelleine-I exerted a good therapeutic effect on mice with peritonitis caused by E. coli [ 109 ]. Promising results confirming in vivo antimicrobial activity of RJ were also obtained by Gunaldi et al [ 110 ]. The authors conducted an evaluation of RJ performance in an implant-related infection model in rats.…”
Section: Antimicrobial Properties Of Bee Productssupporting
confidence: 66%
See 1 more Smart Citation
“…In an in vivo experiment on a mouse model, they showed that jelleine-I exerted a good therapeutic effect on mice with peritonitis caused by E. coli [ 109 ]. Promising results confirming in vivo antimicrobial activity of RJ were also obtained by Gunaldi et al [ 110 ]. The authors conducted an evaluation of RJ performance in an implant-related infection model in rats.…”
Section: Antimicrobial Properties Of Bee Productssupporting
confidence: 66%
“…The authors conducted an evaluation of RJ performance in an implant-related infection model in rats. RJ did not prevent MRSA infection but markedly reduced its severity in a group of spinal implant rats inoculated with bacteria and treated with RJ, compared with untreated rats [ 110 ].…”
Section: Antimicrobial Properties Of Bee Productsmentioning
confidence: 99%
“…In 2013, Cashman et al 72 modified the rat surgical model of infection using a titanium ligating clip and used this model to assess the ability and efficiency of a new generation of fibrin tissue sealant to deliver antibiotics to the surgical site. This model was also used to determine whether royal jelly had a preventive role in spinal infections in rats 73 .…”
Section: Rat Modelsmentioning
confidence: 99%
“…However, several authors conirmed that these products also reveal some antimicrobial potential. Boukraa and coworkers revealed that MIC value for royal jelly against S. aureus is about 2% (v/v) [57], and the group of Gunaldi [58] when using this product obtained promising results in the preservation of implant-related infection in rats. The activity of royal jelly is probably a consequence of presence within composition of this product some peptides that inhibit growth of bacteria including members of the genus Staphylococcus [59].…”
Section: Other Bee Products: Pollen and Royal Jellymentioning
confidence: 99%